A Convenient and Efficient Strategy for Improving Separation Ability of Capillary Electrophoresis Through Tilting Capillary as Needed - Wenhui Jia; Pingyi Zheng; Yuchen Cui; James J. Bao; Yanmei Xu; Youxin Li (Separations)
The effect of gravity based on the vector sum of gravity and buoyancy forces working spontaneously for all species was introduced into capillary electrophoresis (CE) as another important force which cooperated with electrophoretic flow and electro-osmotic flow. Their portion was adjusted by simply tilting the whole of the capillary at an angle during CE running. The related formula was proposed and verified through a series of experiments. After investigating the related parameters, results showed that the gravity effect was significantly affected by additives in the buffer, the length, and the inner diameter of the capillary, and the size of the sample molecule. This made the different ions with opposite or significantly different mobilities to be observed at a CE run. It significantly improved separation efficiencies of some small molecules, chiral compounds, macromolecules and cells when the tilt angles of the capillary were adjusted to a special range predicted through the fitting curve. In addition, micrometer level microspheres and cells were firstly separated by the new CE strategy and the resolutions were more than 1.0. After ingeniously designing the gradient of the tilting angle with time, we were able to further enhance the separation efficiency of the targets. For example, the resolution of lysozyme and ribonuclease A could be increased from 3.691 to 7.342. These indicated the huge potential of the new CE strategy and its gradient mode in separation.